Mengelola risiko kredit dalam perbankan: Tantangan dan strategi di era ketidakpastian ekonomi - Khasanah, Aprilia Nur (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze credit risk management in banking and strategies that can be implemented in the face of economic uncertainty. Credit risk is one of the main risks faced by banks as intermediary institutions, arising from the inability of debtors to fulfill their obligations. High credit risk is reflected in the Non-Performing Loan (NPL) ratio in conventional banks and Non-Performing Financing (NPF) in Islamic banks, which directly impacts asset quality, profitability, liquidity, and public trust. The method used in this study is a qualitative approach with a literature review from various relevant scientific sources. The results of the study indicate that credit risk management requires a comprehensive approach, starting from debtor feasibility analysis using the 5C principle, risk measurement through traditional indicators such as NPL/NPF, to the use of modern models such as Probability of Default (PD), Loss Given Default (LGD), and Exposure at Default (EAD). In addition, the application of financial technology and credit portfolio diversification strategies also play a role in reducing credit risk levels. In conclusion, credit risk has a broad impact on banking stability and performance, making effective and integrated management crucial. In uncertain economic conditions, banks are required to improve the quality of risk management in order to maintain operational sustainability and financial system stability.